2019
DOI: 10.1111/issj.12201
|View full text |Cite
|
Sign up to set email alerts
|

Just married: the synergy between feminist criminology and the Tripartite Cybercrime Framework

Abstract: This article is a theoretical treatment of feminist epistemology of crime, which advocates the centrality of gender as a theoretical starting point for the investigating of digital crimes. It does so by exploring the synergy between the feminist perspectives and the Tripartite Cybercrime Framework (TCF) (which argues that three possible factors motivate cybercrimes – socioeconomic, psychosocial, and geopolitical) to critique mainstream criminology and the meaning of the term “cybercrime”. Additionally, the art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 101 publications
1
19
0
Order By: Relevance
“…Earlier studies also reported the impact of such training on the sense of self-efficacy in dealing with difficult patients [ 27 ]. From the feminist perspective, women find it harder to change their attitudes and sense of self-efficacy because of deeply rooted feminine stereotypes and the social roles they fulfill [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies also reported the impact of such training on the sense of self-efficacy in dealing with difficult patients [ 27 ]. From the feminist perspective, women find it harder to change their attitudes and sense of self-efficacy because of deeply rooted feminine stereotypes and the social roles they fulfill [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The feminist approach provides better insight into gender differences in relation to aggression. According to this concept, women’s and men’s perceptions of aggression are closely connected to cultural socialization and expectations of masculine and feminine sex roles [ 31 ]. Connell and Messerschmidt suggested that the concept of gender hierarchy, masculinity, and male hegemony should be perceived on a local, regional, and global level [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like all poems, my poem above may have many meanings, but the one I highlight here offered me 'greater selfunderstanding, clarification, resolution and control' (Baker and Mazza, 2004: 144). Confident in my ability to develop ideas at a high level of abstraction (see Lazarus, 2019b;Lazarus, 2019c) and act independently with originality in applying new research approaches (see Lazarus, 2018;Lazarus and Okolorie, 2019), I embraced the challenges and responsibilities (e.g. money issues -given that I changed the direction of my PhD route from my initial enrolment, which was a fully funded position to a PhD by Publication path, which I selffunded) of an independent researcher, without knowing precisely what lies beyond 'the publication point' (Lazarus, 2020: 13).…”
Section: My Negative Experiences and Writing Poetrymentioning
confidence: 99%
“…The question indeed embodies sarcasm, a sense of relief, satisfaction and victory. Indeed, my intrinsic motivation merged with the inherent satisfaction in flipping my negative experience and turning it into my achievements has been the impetus behind many publication efforts (see Lazarus and Okolorie, 2019;Lazarus 2019b;Lazarus, 2019c;Lazarus, 2019d;Lazarus et al 2017;Ibrahim and Komulainen, 2016;Ibrahim, 2016a;Ibrahim, 2016b;Rush and Lazarus, 2018) and the methodological innovation developed (see (Lazarus, 2019d). The above stanza highlights that the critical step to a new beginning is to believe that one is possible.…”
Section: My Negative Experiences and Writing Poetrymentioning
confidence: 99%